Religion and Sexuality: Reading the Sixth Commandment (“You Shall Not Commit Adultery”) in the Context of Late Ming China - Tian, Haihua (Religions, 2023)
This article examines concubinage in late Ming China through Foucaudian discourse analysis of sexuality in order to explore different responses to the Sixth Commandment by the Jesuits and Chinese literati. It will be interdisciplinary and conducted by way of philology, sexuality studies, feminist studies, cross-cultural criticism, and inter-religious dialogue. Topics include the relationship between religion and sexuality, concubinage in late Ming China, the Jesuits’ attitude towards concubinage, and the case study of the Confucian Catholic Wang Zheng’s struggle. A cross-cultural study of the Six Commandment not only illustrates the complex interaction between religion, sexuality, and gender but also presents early encounters of the Chinese and Christian cultures and the dialogues between them.